IMPLEMENTASI KESELAMATAN KERJA PADA PEMBUATAN AREA DRILLING RIG DENGAN PENDEKATAN TASK RISK ASSESMENT (STUDI KASUS PADA XYZ INDONESIA DI KALIMANTAN TIMUR) - Komeyni Rusba; Hardiyono Hardiyono; James Evert AL; Impol Siboro; Patunru Pongky; Indrawan Tobarasi (Jurnal Public Policy, 2019)
Implementation of work safety in making an area of things that need to be observed the process from upstream to downstream, because occupational safety lives or is on every task of the work that has been arranged in such a way by the company and is divided completely in each section/division as the function of management in work management . This study discusses the implementation of work safety in the drilling rig area at XYZ Indonesia with the task risk assessment approach in East Kalimantan. The purpose of this study is to describe the achievements of the implementation of work safety in the construction of the drilling rig area in XYZ Indonesia with the task risk assessment approach. From the results of the study, the implementation of work safety in the construction of the drilling rig area in XYZ Indonesia with the task risk assessment approach is to carry out controls that have been regulated based on the procedures and technical guidelines for occupational safety and health of XYZ Indonesia on the work of making drilling locations for 43 activities to reduce risk in each activity.